The Influence of Grain Angle on the Tensile Strength of Wood and Plywood - Jain, J. C.; Ananthanarayana, A. K. (Indian Forester, 1968)
Tensile strength of wood and 3 ply boards of the three species of timbers was evaluated with respect to the inclination Of the fibres. It was found that the plywood is superior to wood at all angles of inclination except when the grains are parallel to the direction of loading.